Metaphoricity and the politics of mobility - Margaroni, Maria; Yiannopoulou, Effie (Thamyris intersecting ;, 2006)
This collection of essays investigates the convergence between the postmodern politics of mobility and a politics of metaphor, a politics, in other words, in the context of which the production and displacement of meaning(s) constitute the major stakes. Ranging from discussions of re-territorialization, multiculturalism, "digisporas" and transnational politics and ethics, to September 11th, the Pentagon's New Map, American legislation on Chinese immigration, Gianni Amelio's film Lamerica, Keith Piper's online installations and Doris Salcedo's Atrabiliarios, the collection aims to follow thre